Spiritualitas Pelayanan dalam Model Kepemimpinan Pastoral Romo Janssen, CM - Fabianus Selatang; Tomas Lastari Hatmoko; Gregorius Kukuh Nugroho (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2023)
Spirituality concerns two things: what one does and what one believes others should do. The first part relates to the act of object, and the second relates to the subject of service. This paper aims to describe the spirituality of service in the pastoral leadership model of Fr. Janssen, CM. The method of research used is qualitative, while the method of data gathering is through focus group discussion, interviews, and documentary studies. Focus groups are seen as an appropriate method because discourse and 'shared opinion' will make the validity of the results of this research more secure. Focus groups and shared opinions utilize the perceptions, experiences, and profound relationship between the sources and Fr. Janssen, CM. The researcher interviewed five key informants. Meanwhile, the documentary study deals with documents that support the interview data. Saldaña's coding method is utilized in data analysis. The data will be processed based on six coding steps. The results of this study show that the spirituality of the ministry of Fr. Janssen, CM is reflected in the transformational leadership model. Transformational leadership gives birth to beliefs that are the basis for pastoral ministry. The leadership model of Fr. Janssen, CM's is a set of values. These values are revealed in service and manifested in a definite way of life. This research significantly contributes to the science of ecclesiology in Indonesia and pastoral leadership in general.